Impurities and electronic localization in graphene bilayers - Ojeda Collado, Hector Pablo (2015)
We analyze the electronic properties of bilayer graphene with Bernal stacking and a low concentration of adatoms. Assuming that the host bilayer lies on top of a substrate, we consider the case where impurities are adsorbed only on the upper layer. We describe nonmagnetic impurities as a single orbital hybridized with carbon's pz states. The effect of impurity doping on the local density of states with and without a gated electric field perpendicular to the layers is analyzed. We look for Anderson localization in the different regimes and estimate the localization length. In the biased system, the field-induced gap is partially filled by strongly localized impurity states. Interestingly, the structure, distribution, and localization length of these states depend on the field polarization.